Raising the Bar for Withdrawal Management: A Patient Centered Path Forward - Itai Danovitch; Maureen P. Boyle (Journal of Addiction Medicine, 2026)
Managing substance withdrawal is often a necessary part of addiction care. However, without treatment of the underlying addiction, patients are at high risk for morbidity and mortality. The Fourth Edition of the ASAM Criteria sets the expectations that withdrawal management programs will have the capacity to provide integrated psychosocial services for the underlying addiction. While implementation of these updated standards will be challenging, particularly in rural and under-resourced areas, it is critical for improving care quality and patient outcomes.